A new vector emerges? Aedes vittatus mosquito (Diptera: Culicidae): habitat and current and future potential global geographic invasion - Aguirre Obando, Oscar Alexander (Revista de Biología Tropical, 2024)
Introduction: The Aedes vittatus mosquito is an important vector of yellow fever in Africa, with vectorial competence for dengue, chikungunya and Zika. Its presence has been reported in some places in Africa, Asia, Europe and – recently – America. However, such information is scattered and with little description of the characteristics of the areas where it inhabits. Objective: Therefore, the aim was to compile records of its occurrence, describe the ecological characteristics of its habitat and estimate its current and future potential global invasion. Methods: A dataset was formed with the first records and global records of the mosquito, which were the basis for describing the habitat of the areas where it is found and together with layers of bioclimatic variables were implemented to estimate, through an ecological niche model (ENM), the areas of potential invasion using the MaxEnt algorithm. Since the native range of A. vittatus is unknown, two hypotheses were proposed for the calibration of accessible áreas, Africa and Asia, based on the genetic information available so far. Results: It is suggested that, regardless of its native area, A. vittatus is currently distributed in all continents in both tropical and subtropical zones, where at higher emissions and high time periods, it could expand into subtropical climates colonizing colder climates. Conclusions: It is estimated that the mosquito can be found on all continents at altitudes between 0 – 2500 m and at temperatures between 15 – 30 °C, being found mainly in tropical coverages and in urban areas being favored probably by transcontinental and terrestrial passive transport networks allowing the invasion of new locations.